Deletion of 22q11 chromosome is associated with postoperative morbidity after unifocalisation surgery. (30th August 2018) - Koth, Andrew; Sidell, Doug; Bauser-Heaton, Holly; Wise-Faberowski, Lisa; Hanley, Frank L.; McElhinney, Doff B.; Asija, Ritu
Abstract: Background: A 22q11 chromosome deletion is common in patients with tetralogy of Fallot, pulmonary atresia, and major aortopulmonary collaterals. We sought to determine whether 22q11 chromosome deletion is associated with increased postoperative morbidity after unifocalisation surgery. Methods: We included all patients with this diagnosis undergoing primary or revision unifocalisation ± ventricular septal defect closure at our institution from 2008 to 2016, and we excluded patients with unknown 22q11 status. Demographic and surgical data were collected. We compared outcomes between those with 22q11 chromosome deletion and those without using non-parametric analysis. Results: We included 180 patients, 41% of whom were documented to have a chromosome 22q11 deletion. Complete unifocalisation was performed in all patients, and intracardiac repair was performed with similar frequency regardless of 22q11 chromosome status. Duration of mechanical ventilation was longer in 22q11 deletion patients. This difference remained significant after adjustment for delayed sternal closure and/or intracardiac repair. Duration of ICU stay was longer in patients with 22q11 deletion, although no longer significant when adjusted for delayed sternal closure and intracardiac repair. Finally, length of hospital stay was longer in 22q11-deleted patients, but this difference was not significant on unadjusted or adjusted analysis. Conclusion: Children with tetralogy of Fallot, pulmonary atresia, and major aortopulmonary collaterals and 22q11 deletion are at risk for greater prolonged mechanical ventilation after unifocalisation surgery. Careful attention should be given to the co-morbidities of this population in the perioperative period to mitigate risks that may complicate the postoperative course.